Exploring the Impact of Sensory Activities on the Development of Entrepreneurial Spirit in Children - Novingky Ferdinand; Taufik Hidayat; Hernawan Hanif; Sugeng Riyanto (Doctoral Program of Social Science, Pasundan University, 2023)
This article explores the impact of sensory activities on fostering an entrepreneurial spirit in children. Sensory activities, involving exercises that stimulate a child’s senses, play a crucial role in cognitive development and can lay the groundwork for entrepreneurial skills. The article emphasizes how these activities enhance creativity, critical thinking, and problem-solving abilities - key components of an entrepreneurial mindset. It discusses how engaging in sensory play, arts and crafts, music, and nature walks not only provides immediate enjoyment but also develops traits like resilience, adaptability, and innovative thinking in children. By promoting a sense of curiosity and exploration, sensory activities contribute to building an entrepreneurial mindset from an early age. This approach is vital in preparing children for the complexities and demands of the future, equipping them with skills necessary for success in an ever-evolving global landscape.